(untitled) (Bangladesh Journal of Urology, 2022)
Introduction: Emphysematous pyelonephritis (EPN) is considered a rare renal infection. It is an acute severe necrotizing infection resulting in the production of gas in the renal parenchyma, collecting system or perinephric tissue. In this report, we describe the clinical, laboratory and imaging findings and in-hospital outcomes of EPN patients who underwent different surgical procedures. Method: This prospective observational study was carried out at BIRDEM General Hospital, Dhaka, Bangladesh between January 2018 and November 2021. Result:A total of 29 patients were recruited to the study (mean age 52.18 + 8.352 year; range 40 – 68 year) including female predominance (89.7%). Comorbidities includes diabetes (96.55%), hypertension (58.6%), acute kidney injury (58.6%), chronic kidney disease (37.9%), renal stones (20.7%), associated hydronephrosis (HDN) or hydroureteronephrosis (HDUN) (27.6%) and multiple comorbidities (93.1%). Neutrophilic leucocytosis with poor glycaemic status was common laboratory findings. CT scan used to confirm the diagnosis and classify EPN. Class 2 EPN (17%), class 3A EPN (26%), class 3B EPN (46%) and class 4 EPN (11%). Escherichia coli was the most common organism identified on urine culture (62%). Along with medical management, intervention includes DJ stenting (24.1%), incision drainage (I/D) with primary closure (65.5%), I/D with open wound (6.9%) and nephrectomy (3.4%). Mean + SD duration of drain tube was 12.36 + 4.83 days. Wound infection rate in I/D with primary closure was 15.8%. No patient died in our series. Conclusion: Multidisciplinary team approach with aggressive medical management and timely interventions are key to decrease mortality in management of EPN. The result of incision drainage with primary wound closure along with a drain tube in situ is promising. Bangladesh J. Urol. 2021; 24(2): 181-187